Barriers and facilitators to diabetes prevention support for women in Malaysia with gestational diabetes mellitus: a qualitative study - Ismail, Irmi Zarina; Benton, Madeleine; Sobri, Hafizah Mahamad; Baharom, Anisah; Guess, Nicola; Goldsmith, Kimberley; Iman, Iklil; Ching, Siew Mooi; Yusof, Barakatun Nisak Mohd; Basri, Nurul Iftida; Salim, Mazatulfazura Sf Binti; Hassan, Faezah; et al. (Elsevier, 2025)
Objectives: To explore the barriers and facilitators to diabetes prevention support among pregnant women in Malaysia. Design: A qualitative study using individual in-depth interviews, analysed using reflexive thematic analysis. Setting: Public health clinics and one central government hospital in Selangor, Malaysia. Participants: Women diagnosed with gestational diabetes mellitus. Results: Sixteen women aged 26 to 41 years, from three different ethnic groups (Malay, Chinese, and Indian) participated in the study. Key barriers to diabetes prevention support included limited access to relevant and usable information; competing health needs during pregnancy; social and cultural priorities overriding self-care; and structural constraints. Facilitators included intrinsic motivation and self-awareness; awareness of future diabetes risk; social and family support; access to trusted and culturally relevant information. All participants reported challenges in maintaining healthy lifestyle practices, particularly related to physical activity and diet during pregnancy. Information on diabetes prevention support was obtained from various sources, including healthcare providers, online platforms, and family members. Conclusion: The findings from this study have significant implications for enhancing diabetes prevention support and informing the potential development of tailored diabetes prevention interventions for women in Malaysia.